Albania : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines the Progress Report for Albania's National Strategy for Socio-Economic Development (NSSED). 2002 was the first year of implementing the NSSED. The implementation process has been oriented toward achieving the annual objectives and in accordance with the program of public priority measures for 2002-04. The experience gained in NSSED implementation, the definition and improvements to objectives and medium-term NSSED measures, the Millennium Development Goals, and Albania's European integration objectives have all contributed to further improvements of the vision and medium and long-term NSSED objectives.